Bifurcation Analysis and Quenching Chaos in Brushless DC Motor Based on Dither Signals (Contemporary Mathematics, 2025)
This study investigates bifurcation and chaos dynamics in brushless direct current (DC) motor (BLDCM) through analyses of time response, Poincare' maps and frequency spectra. A chaos suppression approach is then proposed and detailed. To identify the initiation of chaotic motion in BLDCM, Lyapunov exponents and dimensions are utilized. Subsequently, the study implements the suggested method by introducing an external input, referred to as a dither signal, into the chaotic BLDCM system. The effectiveness of the proposed control method was determined by simulations.
Keywords: bifurcation; chaos; BLDCM; Lyapunov exponent; dither